Erwinia mallotivora sp., a New Pathogen of Papaya (Carica papaya) in Peninsular Malaysia - Amin, Noriha Mat (Molecular Diversity Preservation International (MDPI), 2010)
Erwinia mallotivora was isolated from papaya infected with dieback disease showing the typical symptoms of greasy, water-soaked lesions and spots on leaves. Phylogenetic analysis of 16S rRNA gene sequences showed that the strain belonged to the genus Erwinia and was united in a monophyletic group with E. mallotivora DSM 4565 (AJ233414). Earlier studies had indicated that the causal agent for this disease was E. papayae. However, our current studies, through Koch’s postulate, have confirmed that papaya dieback disease is caused by E. mallotivora. To our knowledge, this is the first new discovery of E. mallotivora as a causal agent of papaya dieback disease in Peninsular Malaysia. Previous reports have suggested that E. mallotivora causes leaf spot in Mallotus japonicus. However, this research confirms it also to be pathogenic to Carica papaya.